2019
DOI: 10.1039/c9ra03214b
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free four-component domino synthetic approach toward versatile multicyclic spirooxindole pyran scaffolds

Abstract: A new versatile strategy involving a sequential four-component reaction of the nitroketene dithioacetals, alkylamine/benzylamine, isatin and various enolizable active methylene structures (pyrazolone, barbituric acid, 1,3-indandione and 2-hydroxy-1,4-naphthoquinone) as precursors under mild and catalyst-free conditions results in the synthesis of new functionalized spirooxindole pyrans named spiro[indoline-3,4 0pyrano[2,3-c]pyrazol], spiro[indoline-3,5 0 -pyrano[2,3-d]pyrimidine], spiro[indeno[1,2-b]pyran-4,3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The final intramolecular O ‐cyclization step allows the formation of the desired multicyclic spirooxindole pyran scaffolds. Despite moderate yields, this convenient one‐pot process comprises simple work‐up procedures and high molecular diversity (17 examples) [175] . Mohebat et al .…”
Section: Spirooxindole Derivativesmentioning
confidence: 99%
“…The final intramolecular O ‐cyclization step allows the formation of the desired multicyclic spirooxindole pyran scaffolds. Despite moderate yields, this convenient one‐pot process comprises simple work‐up procedures and high molecular diversity (17 examples) [175] . Mohebat et al .…”
Section: Spirooxindole Derivativesmentioning
confidence: 99%
“…Dihydropyrano [2,3-c]pyrazole and its derivatives are attractive and fruitful scaffolds in the field of synthetic as well as medicinal chemistry having diverse biological activities such as anti-inflammatory, anti-microbial activity, anti-cancer, analgesic and anti-oxidant etc. [62] Tripathi et al reported an eco-friendly and metal-free procedure for the synthesis of pyrano [2,3-c]pyrazoles (73) via a four-component reaction of ethylacetoacetate (69), hydrazine hydrate (70), aromatic aldehydes (71) and malononitrile (72) at room temperature (Scheme 38). [63] The reaction was carried out in solvent-free and catalyst-free conditions exploiting visible light as a promoter.…”
Section: Synthesis Of Pyrazole and Pyrano-pyrazole Derivativesmentioning
confidence: 99%
“…They also found that in the absence of visible light, the yield of the product was noticeably decreased to 30 % which specified the importance of light. The authors proposed that ethyl acetoacetate (69) and hydrazine hydrate (70) underwent nucleophilic addition reaction to form 39 A, which through keto-enol tautomerism led to 39 B. Then, malononitrile (72) tautomerized in presence of visible light and reacted with benzaldehyde (71) to form benzylidene malononitrile adduct 39 D which formed a radical 39 E by photochemical activation.…”
Section: Synthesis Of Pyrazole and Pyrano-pyrazole Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterized by highly pronounced biological properties, spirocompounds are representatives of an important category of naturally occurring substances . The spirooxindole skeleton, as the core structure of many pharmacological agents and natural alkaloids with various functional groups taking position at C‐3 of oxindoles, often presents an enhancement in their biological activity . These substances also show diverse activities such as antiproliferative, anti‐inflammatory, antihuman immunodeficiency virus, antihuman respiratory syncytial virus, antidengue virus, anti‐influenza virus agents, and therapeutic value for several clinical illnesses such as obesity, diabetes, gastrointestinal, and urinary disease functioning via β3 adrenoceptor agonism …”
Section: Introductionmentioning
confidence: 99%